Konflik Batin Tokoh Utama Pada Novel Neraka Dunia Karya Nur Sutan Iskandar - Rahayu Nilam Sari; Ismail Nasution (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
The author will discuss the inner conflict of the main character in the novel Neraka Dunia by Nur Sutan Iskandar in this study. This study aims to: (a) describe the form of inner conflict of the main character in the novel Neraka Dunia by Nur Sutan Iskandar; (b) describe the impact of the inner conflict of the main character in the novel Neraka Dunia by Nur Sutan Iskandar. In this study, the author uses literary research and qualitative research methods. The data that the author uses are in the form of character narratives, actions of characters, thoughts of characters, and exposure of the narrator. The author uses the novel Neraka Dunia by Nur Sutan Iskandar as a data source. Data collection and analysis were carried out using the following techniques: (a) reading, understanding, and knowing the contents of the novel; (b) taking inventory of data about plot, characters, and setting; (c) classifying data about the forms, causes, effects, and resolution of inner conflicts. The results of the data are as follows: (a) four forms of inner conflict of the main character in the novel Neraka Dunia by Nur Iskandar, namely the analysis of anxiety, fear, and heartache; (b) four effects of inner conflict, namely self-punishment, shame, curiosity, and guilt.